2009
DOI: 10.1016/j.jacc.2008.10.047
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Cyclooxygenase Inhibition by Low-Dose Aspirin Is Not Reflected Consistently by Platelet Function Assays

Abstract: Platelet cyclooxygenase activity, as reflected by serum TXB(2) levels, is uniformly and persistently suppressed by low-dose aspirin in healthy subjects. However, the effect of aspirin is variably detected by functional assays, potentially leading to misclassification of "responder" as "resistant" phenotypes owing to poor reproducibility of functional measurements. The nonlinearity of the relationship between inhibition of TX production and inhibition of platelet function has important clinical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
234
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(256 citation statements)
references
References 32 publications
17
234
0
5
Order By: Relevance
“…Although a number of small studies have suggested possible benefit from guided therapy in these clinical settings and in children, it is prudent to consider that highly favorable results were reported from early small randomized controlled trials 73 in patients with coronary artery disease before much larger, more definitive randomized controlled trials failed to confirm any benefit from this approach. [74][75][76] There is a possible role for platelet function testing (1) to document patient adherence to antiplatelet therapy or to confirm suspected nonadherence in patients with ischemic events 42,49 and (2) to determine the timing of cardiac surgery following withdrawal of a P2Y 12 inhibitor …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although a number of small studies have suggested possible benefit from guided therapy in these clinical settings and in children, it is prudent to consider that highly favorable results were reported from early small randomized controlled trials 73 in patients with coronary artery disease before much larger, more definitive randomized controlled trials failed to confirm any benefit from this approach. [74][75][76] There is a possible role for platelet function testing (1) to document patient adherence to antiplatelet therapy or to confirm suspected nonadherence in patients with ischemic events 42,49 and (2) to determine the timing of cardiac surgery following withdrawal of a P2Y 12 inhibitor …”
Section: Discussionmentioning
confidence: 99%
“…39 However, if "resistance" is defined in pharmacological terms as the failure of aspirin intake to fully inactivate its target, platelet COX-1, as evidenced by lack of inhibition of thromboxane B 2 generation, then aspirin resistance is either a very rare phenomenon [40][41][42] or does not exist. 17 Based on this pharmacologic definition, a study of 400 healthy volunteers failed to identify a single case of aspirin resistance.…”
Section: 34-37mentioning
confidence: 99%
See 2 more Smart Citations
“…Reported rates of aspirin resistance have varied widely in PFT assays, but studies that have specifically measured levels of COX-1 acetylation or thromboxane B 2 in the blood have failed to detect significant rates of aspirin resistance in healthy individuals when compliance is ensured. 9,21,31,41,42 In studies on clopidogrel, resistance is most commonly defined as high on-treatment platelet reactivity to ADP by the P2Y12 receptor, indicating limited platelet inhibition. Given the variability of the PFT assays employed and their respective cut-off values for defining high on-treatment platelet reactivity, reported rates of clopidogrel resistance have varied from as low as 16% to as high as 50%.…”
Section: Antiplatelet Drug Resistancementioning
confidence: 99%